2016
DOI: 10.1186/s40064-016-3675-2
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-method study of the efficacy of physical activity consultation as an adjunct to standard smoking cessation treatment among male smokers in Malaysia

Abstract: Background This study examined the effectiveness of using Physical Activity Consultation (PAC) as an addition to the standard smoking cessation treatment in Malaysia. We explored participants’ experiences in terms of physical activity and smoking abstinence with the combined PAC and smoking cessation intervention.MethodsWalk-in smokers from a local smoking cessation clinic volunteered for the 8-week intervention program, while undergoing standard smoking cessation treatment. In Week 1, a facilitator conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…In line with this finding, a previous Iranian study reported that cigarette cessation was easier in physically active smokers than inactive individuals (27). This finding was also reported in a study from Malaysia (33). We found no study indicating a positive or non-significant association between physical activity and smoking.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this finding, a previous Iranian study reported that cigarette cessation was easier in physically active smokers than inactive individuals (27). This finding was also reported in a study from Malaysia (33). We found no study indicating a positive or non-significant association between physical activity and smoking.…”
Section: Discussionsupporting
confidence: 90%
“…The dropout rate was 64 per cent from the beginning of the programme to final follow-up. No clear factor for dropout was identified beyond the suggestion that drop-outs may have been more likely to be employed, supporting Lee et al (2016), and less sedentary, but less healthy at intake. Studies that have examined dropout from smoking cessation programs in non-clinical samples have found widely varying attrition rates.…”
Section: Limitationsmentioning
confidence: 99%
“…11 Several studies have found that smokers' self-efficacy attempting to quit smoking affected smoking cessation and interventions; it aided in long-term smoking reductions. [12][13][14] If the attitude and subjective norms are favourable, smokers would be motivated to quit smoking with greater perceived behavioral control. However, it needs a firm intention and motivation.…”
Section: Introductionmentioning
confidence: 99%